2020
DOI: 10.1177/1533033820983081
|View full text |Cite
|
Sign up to set email alerts
|

Combined p53 and Bcl2 Immunophenotypes in Prognosis of Vietnamese Invasive Breast Carcinoma: A Single Institutional Retrospective Analysis

Abstract: Background: Aberrant of p53 and Bcl2 genes cause changes in the quantity and quality of their proteins and contribute to the pathogenesis of some cancer types including breast cancer. Expression of p53 and Bcl2 were associated to adverse clinical outcomes in breast cancer. Purpose: To predict the survival outcomes of invasive breast cancer in Vietnam, using immunohistochemical expression of p53, Bcl2 proteins. Methods: The current study was conducted on 526 breast cancer patients who had surgical operations, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Another study found that BCL2 was strongly linked to better clinicopathological factors, including small size of tumors, lower histological grade, less lymph node metastasis, and lymphatic invasion 48 . In Czech, study by Čečka et al, 30 revealed no significant correlation between BCL2 with tumor size and grade.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that BCL2 was strongly linked to better clinicopathological factors, including small size of tumors, lower histological grade, less lymph node metastasis, and lymphatic invasion 48 . In Czech, study by Čečka et al, 30 revealed no significant correlation between BCL2 with tumor size and grade.…”
Section: Discussionmentioning
confidence: 99%
“…During quiescence, LEF1 appeared in the outermost layer of the bulge region, and its expression was also markedly enhanced in the inner root sheath below the bulge region, similar to the localization of stem cell markers. BCL2 is an apoptosis-inhibiting gene and is considered an influential factor in tumor cell production and proliferation, and it may play a role in the HF growth cycle and morphogenesis [57][58][59][60]. Its expression in the follicular epithelium is dependent on the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Экспрессия мутантного p53 может быть связана с потерей экспрессии Bcl-2 и повышением клеточной пролиферации. В исследованиях показана негативная прогностическая роль гиперэкспрессии белка р53, который ассоциирован с низкой степенью дифференцировки, отсутствием экспрессии рецепторов эстрогена, отсутствием ответа на химиотерапию, снижением показателей выживаемости [27]. В исследованиях обнаружено, что большинство опухолей при тройном негативном фенотипе РМЖ с мутацией BRCA1 также демонстрируют и наличие мутации TP53 [28].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Repr...unclassified